SURGICAL TREATMENT OF SPONDYLOLIS SPONDYLOLISTHESIS: HISTORY AND CURRENT STATUS OF THE PROBLEM (REVIEW) - A. N. Rott; V. V. Kurnosenkov (Travmatologiâ i Ortopediâ Rossii, 2011)
Based on the scientific literature analysis the authors highlight the etiology and the existing classifications of spondylolisis spondylolisthesis, the historical stages of surgical treatment of this disease. The advantages and shortcomings of current methods and ways of treatment, possible complications are described.